Analisis Tantangan dalam Pengembangan Ekowisata Pesisir Berkelanjutan di Pantai Sri Mersing, Desa Kuala Lama - Meilinda Suriani Harefa; Elsa Kardiana; Desi Murni AR; Nurul Mutia Azzahara; May Hafizah; Grace Holyvia J.Dachi (Lembaga Pengembangan Kinerja Dosen, 2025)
This research examines the development of sustainable coastal ecotourism at Sri Mersing Beach, Kuala Lama Village, Serdang Bedagai Regency. This area has tourism potential in the form of a 2-kilometer stretch of white sand beach, a gentle beach gradient, and a row of pine trees that provide a distinctive shade. The research was conducted in March-April 2025 using a descriptive qualitative approach with a case study method. Data collection was carried out through direct observation, in-depth interviews with key informants selected through purposive sampling, and literature study. The research results indicate that the development of ecotourism in this area faces several major challenges, such as limited infrastructure, suboptimal waste management, low capacity of local human resources, and weak institutional coordination. Nevertheless, the preserved natural potential and local uniqueness provide significant opportunities for the development of sustainable ecotourism. This research recommends an integrated approach that involves all stakeholders in formulating eco-tourism development strategies that consider economic, social, and environmental aspects.